PENGARUH MODAL KERJA, PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Purba, Ramina; Efriyenti, Dian (LPPM Universitas Putera Batam, 2019)
The establishment of a company is always backedi up with the aim of earning profit or profit, to increase profits the company must have good performance and prospects. The purpose of this study is to find out how much influence and to find out more about the effect of working capital, accounts receivable turnover and inventory turnover on profitability (ROA) of companies listed on the Indonesiai Stock Exchange. The population in this study were companies listed on the Indonesia Stock Exchange. The technique used in the study was Purposive sampling with criteria that met the requirements and obtained 8 manufacturing companies that were included with the data within a period of 5 years to obtain a sample of 40. Secondary data used in the study. The results showed partially that the working capital variable had a significant effect on ROA, while the accounts receivable variable and inventory turnover did not affect ROA. The results of the analysis simultaneously or overall show that the variables of working capital, accounts receivable turnover and inventory turnover together have ai significant effect on ROA.